Parametrization of prompt neutron yields from photofission fragments of actinide nuclei for the giant dipole resonance energy range - Lengyel, A.I.; Parlag, O.O.; Maslyuk, V.T.; Kibkalo, Yu.V.; Romanyuk, M.I. (Вопросы атомной науки и техники, 2014)
The dependence of prompt neutron yield on fragment mass ν(A) of photofission of actinide nuclei ²³²Th, ²³⁵U and ²³⁸U in the giant dipole resonance energy range has been parameterized. This allows us to describe the observed changes of saw-tooth behavior of neutron yield from the light and heavy fragments using few energy and nucleon composition dependent free parameters and to predict ν(A) for Pu isotopes.